Lost in a good book : a novel - Fforde, Jasper (Thursday Next, 2002)
Thursday works for Special Ops in the Literary Detectives division. She's made an enemy of the corrupt Goliath Corporation, which manufactures absolutely everything, by imprisoning one of its executives, Jack Schitt, in the pages of Poe's The Raven. In return, the corporation eradicates her new husband, Landen. Since no one really dies in this chronologically fluid universe, Landen could be restored-but Goliath won't do it until Thursday brings back Schitt.